2011
DOI: 10.1097/cnq.0b013e31821c67d5
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Satisfaction, Burnout, and Secondary Traumatic Stress in Heart and Vascular Nurses

Abstract: Objectives for this project were to determine the prevalence of compassion satisfaction (CS), burnout, and secondary traumatic stress (STS) in heart and vascular nurses to confirm whether differences exist between intensive care and intermediate care nurses. The Professional Quality of Life Scale Compassion Satisfaction and Compassion Fatigue: Version 5 developed by Stamm (2009) was used. Results showed that nurses who work in the heart and vascular intermediate care unit had average to high scores of CS, low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
3
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 16 publications
5
54
3
7
Order By: Relevance
“…Staff nurses with 6 to 10 years of experience had higher burnout and lower compassion satisfaction scores than did nurses with less experience; nurses with 11 to 20 years of experience had the highest degree of compassion fatigue. 25 Although the findings of these studies 23,25,28 differ, collectively they indicate that differences in age and experience can affect ProQOL, and therefore further study is warranted to fully examine this relationship. The relationship between highest educational degree and ProQOL scores also implies some differences.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Staff nurses with 6 to 10 years of experience had higher burnout and lower compassion satisfaction scores than did nurses with less experience; nurses with 11 to 20 years of experience had the highest degree of compassion fatigue. 25 Although the findings of these studies 23,25,28 differ, collectively they indicate that differences in age and experience can affect ProQOL, and therefore further study is warranted to fully examine this relationship. The relationship between highest educational degree and ProQOL scores also implies some differences.…”
Section: Discussionmentioning
confidence: 95%
“…Young et al 23 reported that the degree of burnout was higher on a heart and vascular ICU, which had a larger number of older nurses, than on the heart and vascular intermediate care unit, which had a larger number of younger nurses. These researchers 23 concluded that younger nurses might not have been in the profession long enough for signs of burnout to develop. Finally, Potter et al 25 examined the impact of experience on Pro-QOL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 These findings also suggest that the geriatric medicine nurses are able to connect with patients they care for regardless of the outlook and may lead to purposeful and meaningful interactions between the nurse and their patients. 10 Findings suggest the need to purposely build a supportive environment that prevents professional burnout and compassion fatigue and sustain compassion satisfaction. Department values as expressed through policies and procedures should support staff in balancing work and personal needs, as well as provide for adequate time off, assignment rotations, flexible Professional Quality of Life 7 scheduling, education benefits, and other self-care and development activities.…”
Section: Discussionmentioning
confidence: 99%